MODELLING AND SIMULATION OF BUTANOL FERMENTATION BY CLOSTRIDIUM SACCHAROPERBUTYLACETONICUM N1-4 - Irfan Rafi, Fauz
The need of biofuels nowadays continues to increase. In addition to ethanol, one that is being developed is butanol. Butanol is considered more superior than ethanol because it has higher energy density and less volatile. Butanol can be produced by fermentation by Clostridia bacteria, in this case, Clostridium saccharoperbutylacetonicum N1-4 which is considerably superior because of its growth-adaptability in various type of medium, both sugar and starch-based. On the other hand, simulation of butanol fermentation needs to be conducted because it will be useful for biobutanol plant design and operation. This study aims to model and simulate batch butanol fermentation by Clostridium saccharoperbutylacetonicum N1-4 using Shinto, Grisales A, and Grisales B model. Accuracy of the models is evaluated using residual R2. Parameter of Shinto model is tuned. The models are then applied to determine the effect of initial concentration of glucose and organic acids on the production of butanol by comparison with existing experimental results. Model simulations are carried out with the help of MATLAB R2015b software. The results show that tuned Shinto model (Shinto bms2) is more accurate than the original one, and Grisales B model is more accurate than Grisales A. Grisales B model is accurate for fermentation with wider range of initial glucose concentration compared to Shinto model, also for describing effect of the glucose on butanol production. Shinto bms2 model tends to be accurate for describing the effect of butyrate on butanol production.